تقييم تبني المزيج التسويقي الأخضر الخارجي في شركة جود للصناعات الغذائية (دراسة حالة) - قاسم سامر; سكيف نسرين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aimed to evaluate JOUD Company for Food Industry adoption of elements of exterior green marketing mix. The researcher relied on the case study method, the researcher studied validity depending content validity and compatibility validity, the researcher relied on Alpha Cronbach scale to measure the reliability of study tool, and distributed a questionnaire to JOUD company managers, and interviewed most of them during the field study. The main conclusion is there was a partial adoption of the exterior green marketing mix in JOUD Company for Food Industry. The main recommendations were: there is a need for focus on green customer sand more work to raise environmental awareness in the community. Which contributes to competitiveness strength of the company in the future. هدفت هذه الدّراسة إلى تقييم مدى تبني شركة جود للصناعات الغذائية لعناصر المزيج التسويقي الأخضر الخارجي، وقد اعتمدت الباحثة على منهج دراسة الحالة حيث قامت الباحثة بدراسة اختبار صدق المقياس بالاعتماد على صدق المحتوى وصدق التوافق، كما اعتمدت الباحثة على مقياس إلفا كرونباخ لقياس ثبات أداة الدراسة، وقامت بتوزيع استبانة على مديري شركة جود للصناعات الغذائية، كما قامت بمقابلة معظمهم خلال الدّراسة الميدانيَّة. وكانت النّتيجة الرّئيسة التي توصّلت إليها الباحثة تتلخص في: أن شركة جود تتبنى تطبيق عناصر المزيج التسويقي الأخضر الخارجي بشكل جزئي. أمَّا أهم التّوصيات فكانت: ضرورة الاهتمام بالعملاء الخضر بشكل أكبر والعمل على رفع الوعي البيئي في المجتمع، الأمر الَّذي يسهم في تعزيز القدرة التَّنافسيَّة لدى شركة جود مستقبلاً.